Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 167666 by LEKOUMA last updated on 22/Mar/22

I_n =∫(dx/(cos^n x))  Prove that  I_n =((n−2)/(n−1))I_(n−2) +((sin x)/((n−1)cos^(n−1) x))

In=dxcosnxProvethatIn=n2n1In2+sinx(n1)cosn1x

Commented by peter frank last updated on 22/Mar/22

Reduction formular

Reductionformular

Answered by chhaythean last updated on 22/Mar/22

Solution  I_n =∫(dx/(cos^n x))=∫sec^n xdx  =∫sec^(n−2) xsec^2 xdx  let  { ((u=sec^(n−2) x⇒du=(n−2)sec^(n−2) xtanxdx)),((dv=sec^2 xdx⇒v=tanx)) :}  I_n =sec^(n−2) xtanx−(n−2)∫sec^(n−2) xtan^2 xdx  =sec^(n−2) xtanx−(n−2)∫sec^n xdx+(n−2)∫sec^(n−2) dx  I_n =sec^(n−2) xtanx−(n−2)I_n +(n−2)I_(n−2)   I_n +(n−2)I_n =sec^(n−2) xtanx+(n−2)I_(n−2)   (n−1)I_n =sec^(n−2) xtanx+(n−2)I_(n−2)   I_n =(((1/(cos^(n−2) x))×((sinx)/(cosx)))/(n−1))+((n−2)/(n−1))I_(n−2)   I_n =((n−2)/(n−1))I_(n−2) +((sinx)/(cos^(n−1) x(n−1))) true  So  determinant (((I_n =((n−2)/(n−1))I_(n−2) +((sinx)/((n−1)cos^(n−1) x)) is proved.)))

SolutionIn=dxcosnx=secnxdx=secn2xsec2xdxlet{u=secn2xdu=(n2)secn2xtanxdxdv=sec2xdxv=tanxIn=secn2xtanx(n2)secn2xtan2xdx=secn2xtanx(n2)secnxdx+(n2)secn2dxIn=secn2xtanx(n2)In+(n2)In2In+(n2)In=secn2xtanx+(n2)In2(n1)In=secn2xtanx+(n2)In2In=1cosn2x×sinxcosxn1+n2n1In2In=n2n1In2+sinxcosn1x(n1)trueSoIn=n2n1In2+sinx(n1)cosn1xisproved.

Commented by LEKOUMA last updated on 22/Mar/22

Thanks

Thanks

Terms of Service

Privacy Policy

Contact: info@tinkutara.com